Seasonal Prevalence and Anopheline Mosquito Fauna of Distt. Dehradun (Uttarakhand), India - Sundar Singh*, Anamika Rani and (Recent Research in Science and Technology, 2011)
A study on the seasonal prevalence and faunal diversity of anophelines was investigated at six selected localities of Distt Dehra Dun between January, 2008 to December, 2009. A total of 8403 specimens of anophelines were collected, which belongs to 11 species. The most abundant species was An. subpictus (22.35%) followed by An. culicifacies (20.08%), An. stephensi (10.41%) and An. annularis (9.37%) respectively. While the An. gigas (1.20%) was recorded in least number. The density of anophelines starts to increase in summer season and peaked in rainy season and least in winter season, it was due to more availability of breeding sites in rainy season.